Thymic Carcinosarcoma Consisting of Squamous Cell Carcinomatous and Embryonal Rhabdomyosarcomatous Components - Okudela, Koji; Nakamura, Nabuo; Sano, Jin-yu; Ito, Takaaki; Kitamura, Hitoshi (Pathology, research and practice, 2001)
A case of thymic carcinosarcoma in an 83-year-old Japanese man is presented. He died of superior vena cava syndrome caused by a rapidly enlarged anterior mediastinum tumor eight months after initial symptoms. Autopsy revealed a 16 × 12 × 25 cm-sized, tan yellow, whitish tumor with a multinodular and microcystic appearance located in the left anterior mediastinum, which involved the residual thymus. The tumor had directly invaded the left pleura, and had metastasized to the right lung and spleen. Histologic examinations of the primary tumor showed a sarcomatous component consisting of racquet- or spindle-shaped cells with cross striations, and small nests of atypical squamous cells scattered throughout the tumor; neither transition between the two components nor intermediate cells with both epithelial and mesenchymal features was seen. Electron microscopic and immunohistochemical examinations confirmed the rhabdomyomatous differentiation of the sarcomatoid component. To our knowledge, there have been only two reported cases showing histologic features similar to the present tumor. For the histogenesis of thymic carcinosarcoma, we propose two hypotheses. The first is that sarcomatous cells are derived from carcinomatous cells by tumoral metaplasia. Secondly, that this type of tumor originates from thymic primitive cells with multidirectional differentiation potential. In accordance with the latter, we consider that the present tumor originated from thymic primitive cells. Thymic carcinosarcoma is a highly malignant tumor, and most patients die within a year. Appropriate therapies must be developed.